THE EFFECTIVENESS OF PICTURE POCKET MEDIA IN MULTIPLICATION OF TWO NUMBER IN MATHEMATICS SUBJECTS FOR SECOND GRADE STUDENTS OF SD N 14 RANAH PESISIR - Lili Rismaini; Dewi Devita (Jurnal Ilmu Pendidikan Ahlussunnah, 2023)
This research is motivated by the fact that learning is still teacher-centered. The rapid development of information technology in recent years has changed the paradigm of society in seeking and obtaining information. This technological advancement has also influenced instructional media. Teachers typically use print learning media. This study aims to produce an effective learning media called "picture pockets" to improve student learning outcomes in mathematics. The study can be classified as quantitative research with a quantitative approach, employing a quasi-experimental method. The study was conducted with second-grade students at SD N 14 Ranah Pesisir. The research instrument was developed to assess the effectiveness of the "picture pockets" learning media. The results of this study, at the effectiveness stage, were analyzed using statistical analysis, specifically the Paired Sample Test equation, yielding a sig (2-tailed) value of 0.000 < alpha value of 0.05. This means that the Sig.2-tailed value (0.000) is smaller than the alpha value (0.05). Therefore, it can be concluded that the null hypothesis (Ho) is rejected, and the alternative hypothesis (Hi) is accepted, indicating a significant difference in students' mathematics learning outcomes before and after using the "picture pockets" learning media.